Languishing : how to feel alive again in a world that wears us down - Keyes, Corey L. M. (Crown, 2024)
"The Emory University sociologist who coined the term languishing-low-grade mental weariness that affects our self-esteem, relationships, and motivation-explores the rise of this phenomenon and presents a comprehensive guide to flourishing in a world that demands too much. If you're muddling through the day in a fog, often forgetting why you walked into a room . . . If you feel emotionally flattened, lacking the energy to socialize or feel joy in the small things . . . If you feel an inner void-like something is missing, but you aren't sure what . . . Then this book is for you. Languishing-the state of mental weariness that erodes our self-esteem, motivation, and sense of meaning-can be easy to brush off as the new normal, especially since indifference is one of its symptoms. It's not a synonym for depression and its attendant state of prolonged sadness. Languishers are more likely to feel out of control of their lives, uncertain about what they want from the future, and paralyzed when faced with decisions. Left unchecked, languishing not only impedes our daily functioning but is a gateway to serious mental illness and early mortality. Emory University sociologist Corey Keyes has spent his career studying the causes and costs of languishing-the neglected middle child of mental health. Now Keyes has written the first definitive book on the subject, examining the subtle complexities of languishing before deftly diagnosing the larger forces behind its rise: the false promises of the self-help industrial complex, a global moment of intense fear and loss, and a failing healthcare system focused on treating rather than preventing illness. Ultimately, Keyes presents a groundbreaking approach to breaking the cycles keeping us stuck and finding a path to true flourishing. Unlike self-improvement systems offering quick-fix mood boosts, his framework focuses on functioning well: taking simple but powerful steps to hold our emotions loosely, becoming more accepting of ourselves and others, and carving out daily moments for the activities that create cycles of meaning, connection, and personal growth. Languishing is a must-read for anyone tempted to downplay feelings of demotivation and emptiness as they struggle to haul themselves through the day, and for those eager to build a higher tolerance for adversity and the pressures of modern life. We can expand our vocabulary-and, with it, our potential to flourish"--